PENGARUH MANAJEMEN PERKANTORAN TERHADAP EFEKTIVITAS PELAYANAN PADA UNIT PENGELOLA TEKNIS PUSAT KESEHATAN MASYARAKAT (UPT PUSKESMAS) KECAMATAN LINGGANG BIGUNG KABUPATEN KUTAI BARAT - Muliati Veronikanida (ADMINISTRASI PUBLIK, 2020)
Mulianti Veronikanida, a thesis with the title of influence of office management on the effectiveness of service on the technical Unit of Public Health Center (UPT PUSKESMAS) District Linggang Bigung West Kutai Regency. This research aims to know and illustrate the influence of office management on the effectiveness of services. Analysis of the data used to test the relationship or influence of these variables using analytical instruments coefficient correlation product moment, calculation of analysis using SPSS R 17.0 for Windows program. The population of this research is all employees who are in the government district HEALTH CENTER District Linggang Bigung Kutai Barat Regency. As many as 30 (thirty) employees in the status of civil servants and nurses, including doctors, considered to understand the policies and problems with management Puskesmas Linggang Bigung. Because the population is not very large, the author did not take a sample but the entire population was made a respondent with the census method. Calculation of analysis result correlation Product Moment (Pearson) obtained rhit = 0.609, this is compared to the price-critical price table of the correlation coefficient of Product Moment (Pearson) for n = 30 at a signification rate of 5%, which is 0.325. Or can be said also that Rhit = 0.609 > Rtab = 0.325. This means that there is a relationship in the sense of positive influence between the variables of the office management with the variable effectiveness of service in Linggang Bigung West Kutai Regency. Based on the interpretation of inter-variable relations, the interpretation of the results of the calculation is in the interval 0.600 – 0.799, this indicates there is a relationship that is